2008
DOI: 10.1002/adsc.200800141
|View full text |Cite
|
Sign up to set email alerts
|

New Pathway to C2‐Symmetric Atropoisomeric Bipyridine N,N′‐Dioxides and Solvent Effect in Enantioselective Allylation of Aldehydes

Abstract: The [2 + 2 + 2] cyclotrimerization of 1,7,9,15-hexadecatetrayne with nitriles catalyzed by dicarbonylcyclopentadienylcobalt(I) opened a new pathway for the synthesis of C 2 -symmetrical bis(tetrahydroisoquinolines) that were used as starting material for the preparation of axially chiral bipyridine N,N'-dioxides. The N,N'-dioxides (1 mol%) were found to be highly catalytically active and enantioselective (up to 83% ee) for the asymmetric allylation of aldehydes with allyl(trichloro)silane in various solvents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…The reason for this inversion of the enantioselectivity of hm (R)5 -poly-2b depending on the substrates (3a and 3c) (entries 6 and 8 in Table 1) is not clear at present, but may be due to the electron-withdrawing nitro-substituent of 3c. A similar inversion of the enantioselectivity depending on the substrates was reported by Kotora et al 65 The fact that hm (S)5 -poly-2b with an opposite-handed helicity memory produced the product with the opposite configuration (8% ee (S-rich)) while maintaining its catalytic activity (entry 9) demonstrated that optically active helical polymers bearing achiral, but catalytically active residues as the pendants whose optical activities are solely derived from their static helicity memory indeed work as asymmetric catalysts, leading to the development of switchable asymmetric catalysts.…”
Section: Enantioselective Allylation Catalyzed By Pyridine N-oxide-apsupporting
confidence: 85%
“…The reason for this inversion of the enantioselectivity of hm (R)5 -poly-2b depending on the substrates (3a and 3c) (entries 6 and 8 in Table 1) is not clear at present, but may be due to the electron-withdrawing nitro-substituent of 3c. A similar inversion of the enantioselectivity depending on the substrates was reported by Kotora et al 65 The fact that hm (S)5 -poly-2b with an opposite-handed helicity memory produced the product with the opposite configuration (8% ee (S-rich)) while maintaining its catalytic activity (entry 9) demonstrated that optically active helical polymers bearing achiral, but catalytically active residues as the pendants whose optical activities are solely derived from their static helicity memory indeed work as asymmetric catalysts, leading to the development of switchable asymmetric catalysts.…”
Section: Enantioselective Allylation Catalyzed By Pyridine N-oxide-apsupporting
confidence: 85%
“…Researches mainly concentrate on symmetrically or unsymmetrically substituted chiral bis(tetrahydroisoquinoline) N,N'-dioxides ( Figure 7), which with their structure resemble compound 8. In 2008 Kotora et al synthesized symmetrically substituted by (R)-tetrahydrofuran-2-yl dioxides 32 (see Figure 7), which were tested in the allylation of aromatic [50] as well as aliphatic aldehydes [30]. Catalysts synthesis was based on cyclotrimerization of tetrayne with (R)-tetrahydrofuran-2-carbonitrile, followed by oxidation of received bipyridines by m-CPBA.…”
Section: N-oxides With Central and Axial Chiralitymentioning
confidence: 99%
“…Gratifyingly, the presence of substituents in the α-position (chloro and methyl groups) to the carbonyl group in 4f and 4g led to products 5f and 5g with high enantioselectivity (96 % ee; Table 3, Entries 6 and 7), which was higher than those obtained previously. [26] The allylation of aliphatic α,βunsaturated aldehydes 4h and 4i bearing a methyl group at the α-position led to products 5h and 5i with ee values of 70 and 80 % ee, respectively.…”
Section: Entrymentioning
confidence: 99%
“…[23] Recently, this laboratory developed a procedure for the synthesis of various axially chiral N,NЈ-dioxides with the bipyridine scaffold based on CpCo(CO) 2 -catalyzed [2+2+2]-cyclotrimerization of alkynes (diynes) with nitriles under microwave irradiation. These included axially chiral pyridyl(tetrahydroisoquinoline)s, [22] isoquinolyl(tetrahydrosioquinoline)s, [25] symmetrically 3,3Ј-substituted bis(tetrahydroisoquinolyl)s, [26] and unsymmetrically 3,3Ј-substituted bis(tetrahydroisoquinolyl)s. [27,28] Unsymmetrically 3,3Ј-substituted bis(tetrahydroisoquinolyl)s, in particular, were proven to catalyze the highly enantioselective allylation of aromatic and α,β-unsaturated aldehydes with ee values reaching up to 99 %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation